РЕЗУЛЬТАТИВНІСТЬ ДІЯЛЬНОСТІ НАУКОВО-ПЕДАГОГІЧНОГО ПЕРСОНАЛУ ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДІВ УКРАЇНИ - Качан, Євген; Бакуліна, Наталія (Регіональні аспекти розвитку продуктивних сил України, 2017)
Розглянуто необхідність розвитку компетенцій науково-педагогічного персоналу в сучасних умовах, проаналізовано результативністьі його діяльності у вищих навчальних закладах III – IV рівнів акредитації України, окреслено доцільність застосування кластерного аналізу в таких дослідженнях. Tthe article deals will the necessity of development of jurisdictions personnel for modern terms, suggestions are given in relation to introduction of additional criteria of personnel evaluation , recommendations of higher establishment are given in relation to realization of structural division which are, directed on motivation of teachers to the improvement of processes of teaching and studies, and also development of projects of development of jurisdictions, scientifically pedagogical to the personnel taking into account the map of career for every worker with pointing of necessary jurisdictions and ways of their acquisition.